Communication performance analysis of secondary users in cognitive radio networks under primary user emulation attacks - Shan-shan WANG; Xing-guo LUO; Peng LI (Tongxin xuebao)
Cognitive radio network(CRN)is an effective technology and a hot research direction which could solve the problem of deficient resource and revolutionize utilization.And its safety technology attracted more and more researches.Primary user emulation(PUE)is a typically easily and largely affecting attack.PUE attacked come from both malicious misbehavior secondary users(MMU)and selfish misbehavior secondary users(SMU).The former was studied much more deeply than the later one.Distinguishing MMU and SMU,a four dimensional continuous time markov chain model to analyze the communication performance of normal secondary users under PUE attacks,and typically affected by SMUs was proposed.Furthermore,several PUE detection technologies were compared.The emulation results indicate that the SMU detection mechanism is essential for the PUE attack detection technology,which can improve the detection effects largely.